The alternative sigma factor, σS, affects polyhydroxyalkanoate metabolism in Pseudomonas putida - Raiger-Iustman, L.J. (2008)
To determine whether the stationary sigma factor, σS, influences polyhydroxyalkanoate metabolism in Pseudomonas putida KT2440, an rpoS-negative mutant was constructed to evaluate polyhydroxyalkanoate accumulation and expression of a translational fusion to the promoter region of the genes that code for polyhydroxyalkanoate synthase 1 (phaC1) and polyhydroxyalkanoate depolymerase (phaZ). By comparison with the wild-type, the rpoS mutant showed a higher polyhydroxyalkanoate degradation rate and increased expression of the translational fusion during the stationary growth phase. These results suggest that σS might control the genes involved in polyhydroxyalkanoate metabolism, possibly in an indirect manner. In addition, survival and oxidative stress assays performed under polyhydroxyalkanoate- and nonpolyhydroxyalkanoate- accumulating conditions demonstrated that the accumulated polyhydroxyalkanoate increased the survival and stress tolerance of the rpoS mutant. According to this, polyhydroxyalkanoate accumulation would help cells to overcome the adverse conditions encountered during the stationary phase in the strain that lacks RpoS. © 2008 Federation of European Microbiological Societies. Published by Blackwell Publishing Ltd. All rights reserved.